الكدر الزواجي وعلاقته بالتواصل الزواجي لدى عينة من المتزوجات المتأخرات عن الإنجاب في محافظة الكرك - الطراونة، أحلام حامد حسين; النوايسة، فاطمة عبدالرحيم (الجمعية الأردنية للعلوم التربوية, 2024)
هدفت الدراسة بشكل رئيس الكشف عن طبيعة العلاقة بين الكدر الزواجي والتواصل الزواجي لدى النساء المتأخرات عن الإنجاب في محافظة الكرك، اعتمدت الدراسة لتحقيق أهدافها على المنهج الوصفي الارتباطي، وتطوير مقياسي الكدر الزواجي والتواصل الزواجي، والتي تم التحقق من خصائصهما السيكومترية، تكونت عينة الدراسة من (325) سيدة متزوجة متأخرة عن الإنجاب واللواتي تم اختيارهن بالطريقة القصدية من المراجعات لمراكز تقديم الخدمات الصحية في محافظة الكرك من مستشفى الأمير على بن الحسين العسكري، ومستشفى الكرك الحكومي، ومراكز الأمومة والطفولة في محافظة الكرك. توصلت الدراسة بأن مستوى الكدر الزواجي لدى النساء المتأخرات عن الإنجاب في محافظة الكرك جاء مرتفعا بمتوسط حسابي (4.23)، وأن مستوى التواصل الزواجي جاء منخفضا بمتوسط حسابي (2.01)، وكشفت الدراسة عن وجود علاقة ارتباطية سلبية بين الكدر الزواجي والتواصل الزواجي لدى النساء المتأخرات عن الإنجاب في محافظة الكرك. وأوصت الدراسة بضرورة تقديم برامج إرشادية متخصصة بالنساء المتأخرات عن الإنجاب لزيادة مستوى التواصل الزواجي، ولتخفيف من مستوى الضغوط وحدة الآثار النفسية الناتجة عن الكدر الزواج لديهن. The study aimed mainly to reveal the nature of the relationship between marital distress and marital communication among women who are late in childbearing in the Karak governorate. 325 Married women who were late in childbearing, who were selected intentionally from the audits of health service provision centers in Karak governorate from Prince Ali bin Al Hussein Military Hospital, Karak Governmental Hospital, and Maternity and Childhood Centers in Karak Governorate. The study found that the level of marital distress among women who are late in childbearing in the Karak governorate was high with a mean of (4.23), and that the level of marital communication was low with a mean of (2.01), and the study revealed a negative correlation between marital distress and marital communication among women who are late in childbearing in the Karak governorate. The study recommended the necessity of providing specialized counseling programs for women who are late for childbearing. to increase the level of marital communication, and to reduce the level of pressure and the severity of the psychological effects resulting from the distress of marriage for them.
Keywords: الكدر الزواجي -- المتأخرات عن الإنجاب -- الصحة النفسية -- الأردن